Application of Bioclimatic Architecture Concept in Novotel Suite Surabaya - Diana, Tri Wahyu; Setijanti, Purwanita; Cahyadini, Sarah (Institut Teknologi Sepuluh Nopember, 2020)
The development of technology and industry in both developed and developing countries contributes to improve human life for the better. However, it causes an increase in energy consumption and environmental damage which produces global warming. In Asia, according to the data of ASEAN Center for Energy (ACE), 48% of global warming is generated by buildings. This phenomenon is very influential if it occurs in big cities. One of the ways to respond to this phenomenon is to apply sustainable architecture (bioclimatic architecture). Bioclimatic architecture is an architectural concept related to nature and its environment. In Indonesia, the city of Surabaya is the second-largest city. Surabaya is currently envisioned to be a green and smart city, in order to respond to the issue of global warming which currently becomes the center of discussion of all parties. Surabaya City is the second-largest city in which the real estate/property develops very rapidly, especially in commercial building such as hotels. In response to this, this study aimed to determine the application of the concept of Bioclimatic Architecture in one of the buildings in the city of Surabaya, namely the Hotel. The paradigm used in this study is the postpositivist paradigm. A case study was used as the research methodology with field observation techniques to find out whether the Hotel Novotel Surabaya applies the concept of Bioclimatic architecture. The result showed that Novotel applied the Concept of Bioclimatic Architecture into the buildings with a percentage of 94.3%.